The Role of Parents in the Indonesian Language Learning Process on Elementary School Students' Reading Comprehension Skills - Rika Rahmalia; Asep Nurjamin; Didin Sahidin (Journal of Innovation and Research in Primary Education, 2026)
Parental involvement is widely recognized as a critical determinant of children's reading comprehension development; however, its specific mechanisms and constraints within the Indonesian elementary school context remain insufficiently understood.  This study aimed to describe the nature of parental roles in supporting Indonesian language learning at home, analyze students' reading comprehension profiles, and identify structural barriers inhibiting effective parental engagement.  A quantitative cross-sectional survey design was employed with 40 parent–student dyads at a state elementary school in Garut City. Data were collected through a validated Likert-scale questionnaire (α = 0.87), a reading comprehension test (α = 0.83), and semi-structured interviews, and analyzed using descriptive statistics and thematic analysis.  The majority of students (45.0%) performed at the Adequate level, with pronounced deficits in inferential and evaluative comprehension. Overall parental involvement was moderate (M = 2.53), characterized predominantly by reactive rather than proactive engagement. Three intersecting structural barriers were identified: occupational time constraints, parental literacy competency gaps, and digital media displacement.  Parental disengagement reflects structural constraints rather than motivational deficits, underscoring the need for accessible, evidence-based family literacy programs targeting higher-order comprehension support in Indonesian elementary education.